PENGEMBANGAN MODEL PEMBIAYAAN PENDIDIKAN TERINTEGRASI BERBASIS MANAJEMEN PENDIDIKAN ISLAM UNTUK MENJAMIN KESEJAHTERAAN GURU DAN KEBERLANJUTAN LEMBAGA: STUDI KASUS PADA YAYASAN GENERASI MADANI BANTEN - Fikri, Ahmad; Chumsoni, Amad; Kasronudin; Rabiatul Adawiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The sustainability of Islamic educational institutions and teacher welfare are two strategic aspects closely related to educational management. The high dependence of private educational institutions on tuition fees often creates financial vulnerability, affecting educational quality and the institution’s ability to fulfill teachers’ welfare needs. This study aims to analyze the financial management system implemented by Yayasan Generasi Madani Banten, identify financing strategies used to ensure teacher welfare, and formulate an integrated educational financing model based on Islamic Educational Management that supports institutional sustainability. This research employed a qualitative approach using a case study method. Data were collected through document analysis, observation, and examination of financial management practices implemented in TKIT Generasi Madani, SDIT Peradaban Mulia, and SMP Islam Al-Bashri Boarding School. The analysis was conducted using the perspectives of Islamic Educational Management, Human Capital Theory, Resource-Based Theory, Good Governance, and Sustainable Educational Financing. The findings indicate that the centralized financial management system implemented by the foundation improves supervisory effectiveness, resource allocation efficiency, and financial stability among educational units. Financing strategies supporting teacher welfare include needs-based budgeting, prioritization of human resource expenditures, optimization of student enrollment, operational cost efficiency, development of productive business units, partnerships with communities and business sectors, and philanthropic fundraising through the ODOT (One Day One Thousand) program. This study proposes an integrated educational financing model consisting of centralized financial management, performance-based budgeting, cross-subsidization among educational units, income diversification, reserve fund establishment, periodic internal auditing, and prioritization of teacher welfare. The proposed model contributes to strengthening financial governance, improving teacher welfare, and ensuring the sustainability of Islamic educational institutions.